Novel Three-Dimensional Resolution of a pH and Ultraviolet-Visible Absorption Spectral Dataset for the Determination of Desloratadine in a Pharmaceutical Product and Its Acid Dissociation Constant. (12th August 2020) - Dinç, Erdal; Ünal, Nazangül; Ertekin, Zehra Ceren
Abstract: Three-way data analysis (or multi-way data analysis) of higher-order records is required to develop new and potential resolution methods to reveal multiple latent information or hidden features from multicomponent systems in presence of unknown interferences. This article presents a new application of parallel factor analysis (PARAFAC), which is one of the multiway analysis techniques, to quantify desloratadine in sirup and to simultaneously determine its acid dissociation constant (pKa ) in the presence of spectral interferences without using complex and expensive instrumental methods. The three-dimensional pH-absorbance dataset, which was obtained as a function of wavelength, pH and concentration, was decomposed using the PARAFAC algorithm to obtain the estimated spectral, pH and relative concentration profiles of acid-base pair of desloratadine and sirup excipients. The quantity of the drug in sirup formulation was calculated from the estimated relative concentration profile, which was one of the three modes. At the same time, the acid dissociation constant of desloratadine was determined using the estimated pH profile of the acid and base species in their equilibrium. The applicability of the PARAFAC method was confirmed by the analysis of validation samples. In the practical application of the PARAFAC method to real samples, successful results were reported for the quality control of a sirup formulation containing desloratadine and for the estimation of desloratadine's pKa value. The PARAFAC assay results were compared to results obtained by ultra-performance liquid chromatography (UPLC).